Temperature-Dependent Respiration Kinetics and Preliminary Shelf-Life Estimation of Namnam Fruit (Cynometra cauliflora) - Aulia Brilliantina; Findi Citra Kusumasari; Emi Kurniawati; Syaiful Bachri (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Postharvest deterioration of tropical fruits is strongly influenced by respiration activity, which is highly sensitive to storage temperature. However, respiration kinetics data for underutilized fruits, such as namnam (Cynometra cauliflora), remain limited, restricting the development of effective storage strategies. Objective: This study aimed to analyze the effects of storage temperature on respiration kinetics and estimate the preliminary shelf life of namnam fruit using kinetic modeling approaches. Method: Namnam fruits were stored at 10°C, 20°C, and 30°C and evaluated using a closed-system CO₂ absorption method with triplicate measurements. Respiration rates were analyzed using linear regression, the Arrhenius model, Q10 temperature coefficients, and a zero-order degradation model for shelf-life estimation. Result: Respiration rates increased with increasing temperature, showing a strong linear relationship (R² = 0.9984). Arrhenius analysis yielded an apparent activation energy of 27.3 kJ mol⁻¹ with a moderate model fit (R² = 0.6682). Q10 values ranged from 1.45 to 1.68, indicating moderate temperature sensitivity. The estimated shelf life decreased from 13.46 days at 10°C to 9.06 days at 20°C and 6.26 days at 30°C. Conclusion: Lower storage temperatures effectively reduced respiratory activity and extended shelf life; however, respiration-based estimates should be validated using direct quality parameters before commercial application.